Perancangan Dan Pembuatan Digital Promosi Berbasis Web Untuk Malvariota - Delia Ananda Rahmawati (Applied Business and Administration Journal, 2022)
Promotional activities are very important in running a business to market goods or services. Now online is getting tougher so companies need to increase their promotions. Business competitors online especially similar products, could be the main reason for the decline in Malvariota's sales. In order to survive in the midst of online efforts are being made to design and create web-based digital promotions using the Content Management System (CMS) WordPress. The plugins used are Elementor and Yoast SEO. This project has been piloted by interviewing the owners of Malvariota and distributing questionnaires to users. From the results of the interview, it shows that the website has been assessed as very good and in accordance with the needs. The results of the questionnaire show that each question indicator falls into the good and very good categories with respondents' opinions tending to be uniform.